Age and phenology control photosynthesis and leaf traits in the understory woody species, Rhamnus cathartica and Prunus serotina. Issue 6 (30th September 2022) - Heskel, Mary; Pengra, Jean; Kruper, Ally; Anderson, Michael D; Dosch, Jerald J; Goldstein, Lianna; Hahn, Shannon; Hoffman, Sarah
Abstract: Understory plants are often inadequately represented or neglected within analyses of forest ecosystem productivity. Further, the potential impacts of the biological factors of age class and growth form on carbon cycling physiology, and how it may vary across the growing season and amongst species of different native/non-native status, have not been thoroughly considered. Our study examines photosynthesis and associated physical leaf traits in two understory woody species, Rhamnus cathartica, introduced and invasive in North America, and Prunus serotina, a common subcanopy species native to North America. We estimated leaf-level photosynthesis as measured through light and carbon dioxide response curves, dark-adapted chlorophyll fluorescence and leaf traits (leaf mass per area and stomatal density) for each combination of species and age class at plots in the understory of a temperate deciduous research forest in the US Upper Midwest at two time points during the growing season, late spring (late May) and mid-summer (mid-July). Carbon assimilation rates from light response curves ( A sat, A 400 ) and fluorescence capacity estimate F v / F m all increased between the two measurement points in both species and age class. Estimates of carbon reaction capacity ( V cmax and J max ) exhibited a different directional response to seasonal development, declining in seedlings of both species and P. serotina trees (~8–37 % reduction in V cmax, ~9–34 % reduction in J max ), though increased in trees of R. cathartica (+24 % in V cmax, +9 % in J max ). Divergent responses in photosynthetic parameters amongst these factors may be explained by species differences in leaf mass per area and stomatal density, which together are likely influenced by both growth form, canopy position and ontogeny. Overall, we believe our findings suggest complex, varied influences on photosynthesis that indicate environmental and biological plasticity which may contribute to the historic and continued expansion of R. cathartica in the US Upper Midwest region. Abstract : Shaded, understory leaves are often under-represented when considering forest productivity. Our study closely examines how two common understory woody species vary in photosynthesis and leaf traits through the growing season in a temperate forest, and how this relates to their age class and status as native and non-native, invasive species. We found varied responses that overall suggest competitive carbon gain and light use strategies of the invasive shrub, Rhamnus cathartica, which may help to explain its sustained dominance in the region.